2004
DOI: 10.1111/j.1524-4725.2004.30018.x
|View full text |Cite
|
Sign up to set email alerts
|

Superficial Leiomyosarcoma Treated With Mohs Micrographic Surgery

Abstract: The overall cure rate of leiomyosarcoma treated by MMS is 87%, which compares favorably to wide excision and offers the advantage of tissue sparing. Immunosuppression may promote aggressive tumor behavior. Deeply invasive tumors may result in cutaneous or distant metastases regardless of the method of excision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 19 publications
1
11
1
1
Order By: Relevance
“…Although superficial lesions may show associated skin changes such as discoloration, ulceration and umbilication, 2,4,16,29 clinical impressions might include not only benign lesions, such as a lipoma, cyst, keloid, nevus, dermatofibroma and neurofibroma 3,23,29 but also malignant entities such as basal cell carcinoma, squamous cell carcinoma, dermatofibrosarcoma protuberans and malignant fibrous histiocytoma. 3,29,32,34 This study likewise showed a heterogenous list of clinical differential diagnoses, reinforcing the suggestion that the clinical appearance of SLMS is not at all specific and may not necessarily raise the suspicion of a malignancy.…”
Section: Discussionsupporting
confidence: 71%
“…Although superficial lesions may show associated skin changes such as discoloration, ulceration and umbilication, 2,4,16,29 clinical impressions might include not only benign lesions, such as a lipoma, cyst, keloid, nevus, dermatofibroma and neurofibroma 3,23,29 but also malignant entities such as basal cell carcinoma, squamous cell carcinoma, dermatofibrosarcoma protuberans and malignant fibrous histiocytoma. 3,29,32,34 This study likewise showed a heterogenous list of clinical differential diagnoses, reinforcing the suggestion that the clinical appearance of SLMS is not at all specific and may not necessarily raise the suspicion of a malignancy.…”
Section: Discussionsupporting
confidence: 71%
“…[20] Narrow margin excision[13] and even Mohs micrographic surgery have also been used. [10, 11, 28] While several small case series using Mohs resection have been described, recurrences have been reported with long-term follow up. Heuther and colleauges reported a 14% incidence of recurrence when treating a spindle cell neoplasms of the skin such as cutaneous LMS with Mohs micrographic technique.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of margins have been described as being appropriate for resection in the literature including narrow excision, wide excision or even Mohs micrographic surgery. [10-14] However, no consensus as to the most appropriate margin of resection currently exists. We have found that standardization of the surgical margin of resection to be useful at our own institution when treating other rare soft tissue tumors, such as dermatofibrosarcoma protuberans.…”
Section: Introductionmentioning
confidence: 99%
“…Mohs micrographic surgery has been used in the management of superficial leiomyosarcomas with a reported recurrence rate of 0-14%. [1921] In the largest series including 11 patients treated with Mohs surgery, Starling et al .,[20] reported that after a median follow-up of 4.47 years no tumor recurrences were detected. The average tumor size was 4.69 cm 2 and the average size of the surgical defect was 14.95 cm 2 .…”
Section: Discussionmentioning
confidence: 99%